REKRUTMEN BAKAL CALON KEPALA DAERAH PROVINSI RIAU OLEH PARTAI KEADILAN SEJAHTERA DALAM PEMILIHAN UMUM KEPALA DAERAH PROVINSI RIAU TAHUN 2013 - Eka Agustina Indriani; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Political Recruitment ensure continuity and sustainability of political party , as well as a way to recruit and train future leaders . There are various ways to do political recruitment , through personal contact , persuasion , or other means . The purpose of this study was to determine compliance with the requirements given to the Partai Keadilan Sejahtera (PKS) candidate Regional Head of Riau Province which will be supported and know the reason PKS in determining candidate Jon Erizal as Regional Head of Riau Province . The study was conducted in Pekanbaru , which is the key informants in this study is the Chairman of the Board of Regional Leadership ( DPW ) PKS Riau Province , General Secretary PKS Riau Province , Chairman of the Committee on Regional Election Campaign ( KPPW ) Executive Division of the Partai Amanat Nasional (PAN). In collecting the data obtained from the documentations and in-depth interview to the informant . Once the data is collected and analyzed using qualitative analysis. After research in recruiting candidates for regional head , PKS submit three (3 ) requirements that must be met by each candidate , namely : political support , financial support and social support . In fulfillment of financial support , the PKS does not specify the amount of funds to candidates as rumored Regional Head outside , but PKS submitted a proposal containing the winning program. Of the five candidates were selected , PKS sets provide support to Jon Erizal to advance the election of Regional Head of Riau Province in 2013 .Key Word: Political, Recruitment, Political Party